Removal of methylene blue (MB) by bimetallic- metal organic framework - Naser Al Amery; Hussein Rasool Abid; Shaobin Wang; Shaomin Liu (Journal of Applied Materials and Technology, 2020)
In this study, three improved versions of UiO-66 metal organic frameworks (MOFs) were synthesised successfully: Different ratios of Ca+2/Zr+4 were used to synthesise UiO-66, UiO-66-10%Ca and UiO-66-30%Ca. Batch adsorption experiments were achieved to remove MB from wastewater by UiO-66-Ca. UiO-66-10%Ca exhibited the highest adsorption capacity with maximum MB adsorption capacity of 15 mg. g–1 in UiO-66-30%Ca while UiO-66 demonstrated lower MB loading. Langmuir and Freundlich models have been employed to describe isotherms. A kinetics study indicated pseudo first-order and pseudo second-order equations. In addition, an intraparticle diffusion model was utilised. The results presented here may facilitate the further enhancement of UiO-66 MOFs and advance the synthesis of multimetal MOFs in future research.